Cardiovascular safety for once-weekly dulaglutide in type 2 diabetes: a pre-specified meta-analysis of prospectively adjudicated cardiovascular events. Issue 1 (December 2016) - Ferdinand, Keith; Botros, Fady; Atisso, Charles; Sager, Philip
Abstract Background Patients with type 2 diabetes (T2D) have a substantial increased risk for cardiovascular (CV) disease and associated mortality than those without diabetes. Dulaglutide is a once-weekly glucagon-like peptide-1 receptor agonist that is approved for treatment of T2D. Methods This meta-analysis evaluates the CV risk in patients with T2D treated with dulaglutide in 9 randomized safety and efficacy trials. Mean (median) treatment duration was 333 (358) days. Reported CV events were independently adjudicated by a treatment-blinded clinical endpoint committee. The primary measure was a 4-component major adverse CV event (4-component MACE) composite endpoint of death due to CV causes, nonfatal myocardial infarction (MI), nonfatal stroke, or hospitalization for unstable angina. Additional pre-specified endpoints included adjudicated coronary revascularizations, hospitalization for heart failure, and all-cause mortality. A Cox proportional hazards regression model (stratified by study) was used to estimate the hazard ratio (HR) and confidence interval (CI). Tests of treatment effects for the primary endpoint were conducted at a 2-sided alpha level of 0.0198 and a corresponding 98.02 % CI was calculated. Statistical heterogeneity between the strata (studies) was tested by including in the Cox model an interaction term between treatment and strata. Results The analysis included 6010 randomized patients [dulaglutide: 3885; comparator therapy (active or placebo): 2125]; cumulative exposure to dulaglutide or comparator therapy was 3941 and 2223 patient-years, respectively. The demographic and baseline CV disease characteristics were similar across groups. Twenty-six (0.67 %) patients in the dulaglutide group versus 25 (1.18 %) in the comparator group experienced a primary 4-component MACE (HR 0.57; adjusted 98.02 % CI 0.30, 1.10). Results for the 3-component MACE (composite endpoint of death due to CV causes, nonfatal MI or stroke), 6-component MACE (composite endpoint of death due to CV causes, nonfatal MI or stroke, hospitalization for unstable angina or heart failure, or coronary revascularizations) and all-cause mortality were consistent with the primary analysis (HR < 1.0 for all). Conclusions These results suggest that dulaglutide does not increase the risk of major CV events in T2D patients. The ongoing CV outcomes study, Researching CV Events with a Weekly Incretin in Diabetes (REWIND), will further assess CV safety of dulaglutide.